Factors associated with psychotic relapse in patients with schizophrenia in a Pakistani cohort. (5th October 2016) - Ahmad, Irshad; Khalily, Muhammad Tahir; Hallahan, Brian; Shah, Inayat
Abstract: Despite a large body of research evaluating factors associated with the relapse of psychosis in schizophrenia, no studies in Pakistan have been undertaken to date to identify any such factors, including specific cultural factors pertinent to Pakistan. Semistructured interviews and psychometric measures were undertaken with 60 patients diagnosed with schizophrenia (49 male and 11 female) and their caregivers at four psychiatric hospitals in the Peshawar region in Pakistan. Factors significantly associated with psychotic relapse included treatment non‐adherence, comorbid active psychiatric illnesses, poor social support, and high expressed emotion in living environments ( P  < 0.05). The attribution of symptoms to social and cultural values (97%) and a poor knowledge of psychosis by family members (88%) was also prevalent. In addition to many well‐documented factors associated with psychotic relapse, beliefs in social and cultural myths and values were found to be an important, and perhaps treatable, factor associated with relapse of psychosis in Pakistan. The provision of evidence‐based psychotherapeutic interventions, such as behaviour and family therapy and cognitive behaviour therapy for psychosis, could potentially ameliorate the relapse rate of psychosis in Pakistan.